PENGARUH AVERAGE TAX RATE, SIZE,GROWTH, FIXED ASSET RATIO, FINANCIAL LEVERAGE, DAN WORKING CAPITALTERHADAP PROFITABILITY - ERIKA JIMENA ARILYN; BENY BENY; FRANSISCA FRANSISCA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The purpose of this research is to analyze empirically the influence of average tax rate, size, growth, fixed asset ratio, financial leverage, and working capital toward profitability. The object of this research is food and beverage companies that listed in Indonesia Stock Exchange period 2004-2014. The purposive sampling is used as sampling technique, in which only 6 companies meet the sampling criteria, resulting 66 data obsevations used in this research. Data were analyzed using Eviews8 panel data regression with fixed effect model to test the hyphotesis. The results shows that financial leverage and working capital have influence to profitability. In the other hand, average tax rate, size, growth, and fixed asset ratio have no influence to profitability. Overall, the independent variables influence financial leverage simultaneously.